Narrative, identity and the Kierkegaardian self - Lippitt, John; Stokes, Patrick, 1978- (Edinburgh University Press, 2015)
Is each of us the main character in a story we tell about ourselves, or is this narrative understanding of selfhood misguided and possibly harmful? Are selves and persons the same thing? And what does the possibility of sudden death mean for our ability to understand the narrative of ourselves? These questions have been much discussed both in recent philosophy and by scholars grappling with the work of the enigmatic 19th-century thinker SÃıren Kierkegaard. For the first time, this collection brings together figures in both contemporary philosophy and Kierkegaard studies to explore pressing issues in the philosophy of personal identity and moral psychology. It serves both to advance important ongoing discussions of selfhood and to explore the light that, 200 years after his birth, Kierkegaard is still able to shed on contemporary problems. Brings together leading figures in a central philosophical debate of ongoing significance: personal identity Engages with a range of questions of vital importance for the debate about narrative selfhood Demonstrates Kierkegaard's capacity to generate new and illuminating insights for contemporary discussions across a range of traditions